Social networks and its impact on knowledge management - Rashid, Ammar; Wang, William Y. C.; Hashim, Kamarul Faizal (2011)
Given the growing interest and popularity of the social network studies at an individual and organizational level, this paper present critical review of literature, identify gaps and appraise current trends and limitations. Nowadays, the topic of social networks is generally viewed from technology perspective; that is to study the adoption and impact of social networking tools and completely ignore the managerial aspect of social networks.In this paper we argue that organization can leverage the power of social networks for performance, growth and eliminate collaboration inefficiencies.This paper also highlights the importance of network analysis at an organizational level and its role in knowledge sharing processes.This paper ends with highlighting the academic and practitioner implications on future research.